VISUALISASI PENGAJARAN MATEMATIKA SMA DENGAN GEOGEBRA - Hedi, Hedi; Yuliyawati, Sri Nur; Hazma, Hazma; Suryani, Anny; Mulyadi, Ahmad Deni (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
In the teaching process, teachers are expected to be creative and innovative in delivering the subject matter of teaching. One of the methods that can be used is visualizing mathematics teaching using GeoGebra software. However, many teachers need help understanding how to use this software. Therefore, training is needed to visualize mathematical concepts to help teachers teach mathematics in their classes. Mathematics teaching can be visualized with the help of GeoGebra so that it can improve student understanding. With this media, concepts, formula derivations, problem-solving, and their applications can be visualized more clearly. This makes mathematics teaching more explorative because students can directly observe the relationship between analytical and visual representations of a concept and the relationship between mathematical concepts. From this activity, partner teachers benefit from increasing their ability to use GeoGebra software to support the teaching and learning process (KBM). The implementation of this training is in three steps. The first step is the formulation of a tutorial module for visualizing mathematics teaching using GeoGebra. The second step is the implementation of training activities which include pretests, explanations of the subject matter, and practices for visualizing mathematics teaching with GeoGebra. The third step is the final evaluation (posttest). At the end of the training, almost all participants mastered the training topics and only a small number had not mastered it. So, it was concluded that the competence of visualizing mathematics teaching with GeoGebra of partner teachers who attended the training increased. This competence greatly supports the implementation of mathematics teaching in the classroom and makes students more enthusiastic.